2022
DOI: 10.46549/jipvet.v11i3.167
|View full text |Cite
|
Sign up to set email alerts
|

Efek Temperature Humidity Index terhadap Konsumsi Air Minum dan Performans Ayam Kampung Super dengan Pemberian Enkapsulasi Fitobiotik Minyak Buah Merah

Abstract: Ayam kampung super merupakan salah satu ayam kampung yang ditingkatkan performannya dengan perkawinan silang. Akan tetapi, perkawinan silang tidak serta merta memperbaiki performan. Ada beberapa hal lain yang mempengaruhi performan yaitu lingkungan dan feed additive. Oleh karena itu, tujuan dari penelitian ini adalah untuk mengetahui pengaruh Temperature Humidity Index dan pemberian enkapsulasi fitobiotik minyak buah merah terhadap konsumsi air minum dan performans ayam kampung super. Materi yang digunakan ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To maintain the fluid balance in their body, quail experiencing oxidative stress will increase their water intake. According to Syaefullah et al (2021), poultry typically consumes 1.6-2.2 times more water than feed at normal temperatures. Meanwhile, a study found that the coconut shell liquid smoke intake increased linearly with increasing doses, even though there was no significant difference in water intake.…”
Section: Quail Performancementioning
confidence: 99%
“…To maintain the fluid balance in their body, quail experiencing oxidative stress will increase their water intake. According to Syaefullah et al (2021), poultry typically consumes 1.6-2.2 times more water than feed at normal temperatures. Meanwhile, a study found that the coconut shell liquid smoke intake increased linearly with increasing doses, even though there was no significant difference in water intake.…”
Section: Quail Performancementioning
confidence: 99%
“…The most dominant environmental factor is microclimatic conditions. Microclimate is the microclimatic conditions inside the cage (Syaefullah, et al, 2021). The microclimates measured in this study was air temperature, air humidity, and Temperature Humidity Index (THI).…”
Section: Introductionmentioning
confidence: 99%